2022
DOI: 10.1177/00469580221095825
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Providers’ Perspectives Toward the Integration of over the Counter Supplements During COVID-19 Pandemic: A Cross-Sectional Study from Jordan

Abstract: Objective: During COVID-19 pandemic, healthcare providers (HCPs) have been inundated with consultations related to over the counter (OTC) dietary supplements’ protective role. Thus, the present study focused on assessing HCPs perceptions toward OTC products integration during the COVID-19 outbreak. Methods: Pertinent data was collected using validated-online survey comprising four sections: demographics, OTC supplementation perceptions, awareness related to safety of OTC supplements, confidence in recommending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Despite a lack of data to support the role of vitamin D in COVID-19 prevention, the fear of contracting infection and easy access to over the counter supplements has led to high rates of supplement use to boost immunity across the world ( 28 ). While many health care practitioners recommend prophylactic vitamin D supplements to their patients for prevention of COVID-19, ( 29 ), our results suggest that there is not sufficient evidence for this practice. Further, mounting evidence of the risks of high dose vitamin D supplementation suggests that there may be risks associated with this practice ( 30 , 32 , 51 ).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Despite a lack of data to support the role of vitamin D in COVID-19 prevention, the fear of contracting infection and easy access to over the counter supplements has led to high rates of supplement use to boost immunity across the world ( 28 ). While many health care practitioners recommend prophylactic vitamin D supplements to their patients for prevention of COVID-19, ( 29 ), our results suggest that there is not sufficient evidence for this practice. Further, mounting evidence of the risks of high dose vitamin D supplementation suggests that there may be risks associated with this practice ( 30 , 32 , 51 ).…”
Section: Discussionmentioning
confidence: 64%
“…Since the onset of the pandemic, the use of supplements thought to improve immunity has burgeoned ( 28 ). Despite a lack of evidence, a recent study found that nearly 70% of health care workers reported recommending vitamin D supplements to their patients for prevention of COVID-19, regardless of patients’ baseline 25OHD level ( 29 ). Given the widespread use of vitamin D supplements for COVID-19 prevention as well as increasing evidence of potential harms of high-dose vitamin D ( 30 , 31 , 32 ), it is critical to investigate whether and to what extent vitamin D status and supplement use relate to infection risk among healthy individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies exhibited an increase in the use of DSs before and during COVID-19 in Europe [94,95]. There is inadequate evidence to recommend in favor of or against DSs for the prevention or therapy of COVID-19 [96]. Studies published have yielded conflicting results [97][98][99][100].…”
Section: Covid-19 Pandemic and Ds Usementioning
confidence: 99%
“…A cross-sectional survey was designed for this purpose, focusing on orally administered OTC products due to their systemic effects, especially analgesics, antipyretics, cough syrups, antacids, and antihistamines owing to their widespread use in Jordan and their interaction with commonly prescribed medications to treat chronic illnesses such as hypertension and diabetes. [9][10][11] This study aims to assess Pharmacy and Doctor of Pharmacy final years' students' knowledge and perception toward potential DDIs perpetrated by commonly dispensed OTC products. Another aim was to evaluate students' ability to identify prescription from non-prescription medications.…”
Section: Introductionmentioning
confidence: 99%